Errors in English: Description, classification, explanation and remedy - Peter G. Sercombe (Journal of Modern Languages)
My focus, in this paper, is idiosyncratic learner language, in particular written errors produced by learners from predominantly Malay (or Malay-type) language backgrounds. This article adopts what is now an orthodox approach for the analysis of learner idiosyncrasies (van Els et. aI, 1984 and Corder, 1981). This is done at the level of the sentence since there are, as has been suggested (James, 1998: 268), strong grounds for a bottom up approach starting with the most basic levels of error, such as spelling. Evidence has indicated (Harley, 1998) that attention to form is useful even with young learners, especially in dealing with L2 features that have already been identified as problematic and which have L1 equivalents.